1983
DOI: 10.1007/bf00407757
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and turnover of peroxisomes in the yeast Hansenula polymorpha induced by selective inactivation of peroxisomal enzymes

Abstract: Inactivation of peroxisomal enzymes in the yeast Hansenula polymorpha was studied following transfer of cells into cultivation media in which their activity was no longer required for growth. After transfer of methanol-grown cells into media containing glucose - a substrate that fully represses alcohol oxidase synthesis - the rapid inactivation of alcohol oxidase and catalase was paralleled by a disappearance of alcohol oxidase and catalase protein. The rate and extent of this inactivation was dependent upon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0
3

Year Published

1987
1987
1999
1999

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 33 publications
8
144
0
3
Order By: Relevance
“…Clearly, the major change in these spectra is the disappearance of the P~-peak at the low pH position of its titration curve. At the subcellular level these transfers are characterized by a rapid degradation of the large peroxisomes present in the cells (for details on the mechanism of peroxisomal degradation, see Veenhuis et al 1983). Morphometrical analysis of sections of the cells indicated that the peroxisomal volume fraction had decreased approximately 12-fold and amounted to 3.4% of the cytoplasmic volume after 4 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the major change in these spectra is the disappearance of the P~-peak at the low pH position of its titration curve. At the subcellular level these transfers are characterized by a rapid degradation of the large peroxisomes present in the cells (for details on the mechanism of peroxisomal degradation, see Veenhuis et al 1983). Morphometrical analysis of sections of the cells indicated that the peroxisomal volume fraction had decreased approximately 12-fold and amounted to 3.4% of the cytoplasmic volume after 4 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this question can only be properly answered if information becomes available about the molecular machinery involved in the process. In this respect, yeast cells may become extremely useful, because autophagy in yeast is essentially similar to that in mammalian cells (Veenhuis et al, 1983;Baba et al, 1994) and allows the application of molecular genetic procedures in order to identify gene products involved in this process. Complementation studies with yeast mutants deficient in autophagy, obtained by screening on loss of cell viability during nitrogen starvation, have shown the participation of at least 15 different protein components (Tsukada & Ohsumi, 1993), and many more will be identified (Thumm et al, 1994).…”
Section: Control By Amino Acids and Hormonesmentioning
confidence: 99%
“…The peroxisomes are degraded individually by a highly selective autophagic process, and the degradation process appeared to be identical under either of the above conditions. As an initial step, organelles to be degraded were sequestered from the cytosol by a number of membranous layers, closely surrounding the organelle, which most probably were derived from the endoplasmic reticulum; subsequently, hydrolytic enzymes required for the degradation of the microbody contents were supplied by fusion of part of the vacuole with the sequestered organelle (21,27,29,32). The degradation of peroxisomes in H. polymorpha is a rapid process; generally, the total turnover of a single organelle is accomplished within 20 to 45 min (29).…”
mentioning
confidence: 99%